2012
DOI: 10.3758/s13423-012-0289-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of subjective linear orders in probabilistic inferences

Abstract: In probabilistic inferences concerning which of two objects has the larger criterion value (e.g., which of two cities has more inhabitants), participants may recognize both objects, only one, or neither. According to the mentaltoolbox approach, different decision strategies exist for each of these cases, utilizing different probabilistic cues. Possibly, however, participants use these cues to build a subjective rank order that involves all objects, irrespective of their recognition status. The decision process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…First, we restricted analysis to the cities recognized by each participant because it could be argued that criterion knowledge can only be meaningfully applied to cities that are recognized. However, Pohl and Hilbig ( 2012 ) suggested that unrecognized items might also be ordered. Therefore, we also repeated these analyses, including all city names.…”
Section: Resultsmentioning
confidence: 99%
“…First, we restricted analysis to the cities recognized by each participant because it could be argued that criterion knowledge can only be meaningfully applied to cities that are recognized. However, Pohl and Hilbig ( 2012 ) suggested that unrecognized items might also be ordered. Therefore, we also repeated these analyses, including all city names.…”
Section: Resultsmentioning
confidence: 99%